The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/6487989
|View full text |Cite
|
Sign up to set email alerts
|

Identifying miRNAs Associated with the Progression of Keloid through mRNA-miRNA Network Analysis and Validating the Targets of miR-29a-3p in Keloid Fibroblasts

Abstract: Background. Keloid has brought great trouble to people and currently has no uniformly successful treatment. It is urgent to find new targets to effectively prevent the progress of keloid. The current research mainly identifies the differentially expressed genes (DEGs) in keloid through high-throughput sequencing technology and bioinformatics analysis technology, to screen new therapeutic targets and potential biomarkers. However, due to the different samples, different control groups, and small sample sizes, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Multiple research results suggest that miRNAs play a crucial role in scar formation and represent potential targets for scar treatment 28 , 29 . MiRNAs can slow down scar formation by inhibiting the target gene expression and activating or inhibiting related pathways 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple research results suggest that miRNAs play a crucial role in scar formation and represent potential targets for scar treatment 28 , 29 . MiRNAs can slow down scar formation by inhibiting the target gene expression and activating or inhibiting related pathways 30 .…”
Section: Discussionmentioning
confidence: 99%
“…MiR-NAs interact with the 3' untranslated region (UTR) of target mRNAs, thus regulating target gene expression [84]. He et al identified miRNA-29a-3p as a potential biomarker for keloid treatment through mRNA-miRNA network analysis, as it was associated with the progression of keloids [85]. An analysis with a pathway-focused lncRNA microarray identified four lncRNA biomarkers in keloids involved in the Wnt pathway [86].…”
Section: Genetic and Epigenetic Regulation Of Keloidsmentioning
confidence: 99%
“…Of these, three main types of ncRNAs, i.e., miRNA, lncRNA, and circRNA, have been reported to control fibroblast proliferation, migration, invasion, apoptosis, and collagen synthesis through different pathways (92), thereby participating in the keloidogenesis and developmental process. Some researchers consider miR-29a-3p to be a core miRNA that may play an important role in keloid development and progression and may therefore be an effective target for keloid therapy (93). Key processes involved in keloid regulation by lncRNA include the proliferation of fibroblasts, deposition of ECM (94), Wnt signaling (95), Hh signaling (96) and TGF-β signaling (97).…”
Section: Biological Therapy 51 Rna-based Therapymentioning
confidence: 99%